IMPLEMENTATION OF THE RECIPROCAL TEACHING MODEL TO IMPROVE STUDENTS' COGNITIVE ABILITIES AT SAMBAS STATE ELEMENTARY SCHOOL 2 - Ridwan Ridwan; Aslan Aslan; Rona Rona (Adisam Publisher, 2025)
This journal aims to obtain complete and in-depth information on the implementation of the reciprocal teaching model to improve students' cognitive abilities at Madrasah Ibtidaiyah Negeri 2 Sambas until the 2022-2023 academic year. This research uses a qualitative approach with a case study type of research. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Data validity checking techniques use source triangulation, technical triangulation, time triangulation, and member check. The results of the research show that: (1) Teacher planning in implementing the reciprocal teaching model to improve students' cognitive abilities by formulating learning objectives, determining learning experiences, determining teaching and learning activities, providing media and tools, conditioning physical facilities, preparing learning evaluation plans, ( 2) The application of the reciprocal teaching model to improve students' cognitive abilities can be seen during learning. Students are very enthusiastic in carrying out the learning, many questions are asked by other students to the group who are explaining the material in front of the class, (3) Evaluation results in the application of the reciprocal teaching model for improve students' cognitive abilities through evaluative evaluation and formative evaluation.